Development of 3D Animated Story Media Through DRTA Strategy to Improve Reading Comprehension Skills of Elementary School Students - Manggalastawa Manggalastawa; Dhina Cahya Rohim; Fida Maisa Hana; Sinta Nur Kalimah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Reading comprehension is a fundamental literacy skill that supports students’ learning across various subjects. However, observations in elementary schools show that many students still struggle to understand narrative texts due to limited comprehension skills and the lack of engaging and innovative learning materials. At the same time, technological advancements provide opportunities to develop digital learning media that can enhance motivation and comprehension. One promising innovation is the use of 3D animated stories, which can present narrative content in a more vivid, interactive, and meaningful way. This study aims to develop 3D animated story learning media integrated with the Directed Reading Thinking Activity (DRTA) strategy to improve the reading comprehension skills of fourth-grade elementary school students. The research employed the ADDIE development model and was conducted at an elementary school in Kudus Regency, Central Java, Indonesia. The developed product consists of 3D animated learning media and a learning guidebook. Validation results from media experts, subject matter experts, and elementary school learning device experts indicated that the product was highly valid. Field testing showed an improvement in students’ reading comprehension, as reflected by higher posttest scores compared to pretest scores. The effectiveness test revealed a high N-Gain value of 0.73. In addition, practicality assessments through student and teacher questionnaires produced very positive results, with scores of 94% and 87.5%, respectively. These findings indicate that 3D animated stories integrated with the DRTA strategy are effective and practical for improving elementary students’ reading comprehension, particularly in narrative text learning.